Illustrated plant guide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Guide to Plants Tolerant of Arid and Semi-Arid Conditions: nomenclature and potential uses' by E. Weiss, 1989 540pp, ISBN 3 8236 1145 3 price DM98.00 Margraf Scientific Publishers, PO Box 105 D-6092, Weikersheim, GERMANY